BODIPY dyes in photodynamic therapy - Kamkaew, Anyanee; Lim, Siang Hui; Lee, Hong Boon; Kiew, Lik Voon; Chung, Lip Yong; Burgess, Kevin (Royal Society of Chemistry, 2013)
BODIPY dyes tend to be highly fluorescent, but their emissions can be attenuated by adding substituents with appropriate oxidation potentials. Substituents like these have electrons to feed into photoexcited BODIPYs, quenching their fluorescence, thereby generating relatively long-lived triplet states. Singlet oxygen is formed when these triplet states interact with O-3(2). In tissues, this causes cell damage in regions that are illuminated, and this is the basis of photodynamic therapy (PDT). The PDT agents that are currently approved for clinical use do not feature BODIPYs, but there are many reasons to believe that this situation will change. This review summarizes the attributes of BODIPY dyes for PDT, and in some related areas.